Evolution of total column ozone prior to the era of ozone depletion - Brönnimann, Stefan (Frontiers in Earth Science, 2023)
Total column ozone has been monitored for almost a century. The focus of most research of the last 40 years was on the era of ozone depletion and the detection of signs of recovery. However, the question also arises to what extent total column ozone has changed prior to this era. Possible causes could be changes in ozone production (both in the troposphere and stratosphere) due to changing atmospheric composition, changes in solar activity, or climatic changes. In this contribution I discuss the evolution of total column ozone in the 40 years from 1924, when ozone monitoring started, to 1963, which is approximately the time when ozone depletion started to affect the ozone layer. Using long historical measurements as well as an assimilated zonal mean total column ozone dataset, I show that variability was characterised by strong interannual-to-multiannual anomalies, with a small positive trend at northern mid-to high latitudes of ca. 6 DU over the 40 year period. The latitudinal pattern of the trend matches that found in CMIP6 models, but the trend at mid-latitudes is weaker than in the models.